PENGARUH PROMOSI CASHBACK TERHADAP TREN GAYA HIDUP CASHLESS (Survei terhadap followers instagram DANA) - Anindita Putri WIbowo (2021)
The development of industry 4.0 also encourages the development of digital technology in payment transactions, digital payment transactions are used via smartphone, payment transactions via smartphone can be called a mobile payment, this payment is through a digital wallet application, the way mobile payment works is through digital technology by scanning QR code from smartphone. The presence of various digital wallets in Indonesia has an impact on lifestyle changes in payment transactions from cash to non-cash (Cashless). A digital wallets application provide a promotions, on of them is cashback promotion. This research is a research who looks the effect of cashback promotions on cashless lifestyle trends. Cashback promotions is promotions with refund a money into digital wallets consumer that have made a payment in accordance with the terms and conditions that have been determined, DANA is a digital wallets application that provides cashback promotions to the customers. The purpose of this research was to see the effect of the DANA digital wallet cashback promotion on the cashless lifestyle trend for DANA users, especially the official DANA Instagram followers. This research used advertising theory, ATR theory, This research approach is quantitative with correlational research types. Researchers collected data by distributing predetermined questionnaires. The population of this study were DANA Instagram followers, especially DANA users and used purposive sampling technique to draw research samples. The research result of the t test is the t value (6.862) > (0.196) t table so that Ho is rejected and Ha is accepted where there is an effect of cashback promotion on the trend of a cashless lifestyle.